Pengaruh Kredit Terhadap Perilaku Ekonomi Rumahtangga Petani Padi Sawah:Aplikasi Model Ekonomi Rumahtangga Usahatani - rosmiati, mia (SBM ITB, 2012)
This research aims to analyze the effect of credit on farm household economic behavior and evaluate the impact of access to credit sources and reduction of lending rates on farm household economic behavior. This research used survey method. Data analysis using the simultaneous model (2SLS) and simulation model. Data were collected through a survey of household lowland rice farmers in the district of Sumedang, West Java Province. The results showed that farmÃ‚Â householdÃ‚Â as aÃ‚Â unitÃ‚Â of productionÃ‚Â andÃ‚Â consumption respondÃ‚Â positively toÃ‚Â the amount of credit.Ã‚Â The amount of credit, led to theÃ‚Â increased useÃ‚Â of productionÃ‚Â inputs, output Ã‚Â andÃ‚Â farm income, which in turn Ã‚Â willÃ‚Â lead to the increased of consumerÃ‚Â spendingÃ‚Â andÃ‚Â demand forÃ‚Â hired laborÃ‚Â . This indicated that the farm household as a family farming is essentially a household production and household consumption as well, so that production and consumption decisions are not separate, but closely related. Access toÃ‚Â sources of credit is more important than a low lending rates.